¹H NMR handbook of natural products. - Qin, Hailin (Biochemist) (De Gruyter ; Chemistry Industry Press, 2021)
This 6 volume set presents a groundbreaking resource in this branch of natural organic compounds and demonstrates how proton nuclear magnetic resonance (NMR) spectroscopy can be manipulated in structures of natural organic compounds. The book covers 17 kinds amounting to over 10,000 natural organic compounds. The 5th volume mainly illustrates the molecular formula and structures of triterpenoids, phenylpropanoids and steroids.